2004
DOI: 10.2298/jmh0403255s
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein e gene polymorphism as a risk factor for ischemic cerebrovascular disease

Abstract: The possible association of apolipoprotein E (apoE) DNA polymorphism with ischemic cerebrovascular disease was evaluated in 65 patients who had suffered completed stroke or transient ischemic attack and 330 healthy controls. ApoE genotypes were determined by restriction isotyping/MADGE analysis. Significant difference in apoE genotype frequencies between case and control group was observed (p<0.01). Patients affected by ischemic stroke had higher frequency of E4 allele and lower E2 allele than age-matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…McCarron et al [102] found a favorable effect of the ε4 allele on stroke outcome. Stankovic and colleagues [85] reviewed the conflicting results on the importance of the apo alleles in predisposition to IS.…”
Section: Candidate-gene Association Studies Of Ischemic Strokementioning
confidence: 99%
See 2 more Smart Citations
“…McCarron et al [102] found a favorable effect of the ε4 allele on stroke outcome. Stankovic and colleagues [85] reviewed the conflicting results on the importance of the apo alleles in predisposition to IS.…”
Section: Candidate-gene Association Studies Of Ischemic Strokementioning
confidence: 99%
“…Approximately half of all casecontrol studies [26,27,29,33,38,41,45,47,49,51,53,54,57,58,60,64,67,69,71,[73][74][75][76][78][79][80]82,84,85,[89][90][91][93][94][95][96]99,100] showed an increased frequency of the ε4 allele in stroke patients, making it a highly probable risk factor for IS; in four, significant association with large-vessel IS was observed. Three groups described the 2 allele as a risk factor for IS [76,85,94].…”
Section: Candidate-gene Association Studies Of Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…McCarron and colleagues found a favorable effect of E4 on stroke outcome. Stankovi} and colleagues (126) gave detailed description of the conflicting results as to the importance of apoE alleles in predisposition to ischemic stroke.…”
Section: Coagulation and Fibrinolytic System In Strokementioning
confidence: 99%